The financial market effects of the ECB's asset purchase programs - Lewis, Vivien; Roth, Markus (Journal of Financial Stability, 2019)
The European Central Bank's asset purchase programs, while intended to stabilize the economy, may have unintended side effects on financial stability. This paper aims at gauging the effects on financial markets, the banking sector, and lending to non-financial firms. Using a structural vector autoregression analysis, we find a positive effect on output and, after some delay, also on prices in Germany. At the same time, financial stress increases significantly, driven by stock market volatility, higher liquidity premiums and contagion risks. Bank lending in Germany and in the euro area periphery expands, even though borrowing does not become cheaper. This might indicate that more credit is extended to riskier borrowers.